Relationship between energy systems and landscapes. Guidelines and tools for design and management - Ginelli, Elisabetta; Daglio, Laura (TECHNE - Journal of Technology for Architecture and Environment, 2014)
Landscapes undergoing conservation, valorisation, management and reconstruction policies, become a fundamental factor for the local/global development of natural, cultural, human and social potentials of territories. With the contribution of technological design culture, the research, having a strong multidisciplinary character, focuses on managing the relationship between energy systems and landscapes with the general aim of subverting and transforming apparent conflicts in synergies, in order to overcome a sectorial and segmented approach barely based on energy performances. Through the introduction of a complex multidimensional methodology of analysis and evaluation the goal of this work, is to develop standards of acceptability, meta-design criteria and guidelines for design, intro- ducing a methodology for multidimen- sional complex analysis and evaluation, to support Public Authorities.